Hubungan Kecemasan Suami dengan Kesiagaan Suami pada Masa Kehamilan Istri Kota Parepare - Nur Afiah; Bahtiar, Paurianti (Indonesian Journal of Islamic Counseling, 2022)
This research aims to find out the relationship between husband's anxiety and husband's alertness during his wife's pregnancy in the city of Parepare. The benefit of this research is to contribute ideas in the field of science, Islamic guidance and counseling and with the results of this research, it can develop thinking, reasoning, understanding, additional knowledge and thought patterns for writers and parties interested in research. This type of research is quantitative associative. The data collection technique used was a questionnaire. Questionnaires can be in the form of questions or written statements to respondents. Questions or written statements addressed to respondents or informants as an informal data collection technique. The results of this study show that there is a significant relationship between husband's anxiety and husband's alertness during the wife's pregnancy in the city of Parepare with rcount = 0.981 > rtable = 0.195 at a significance level of 5%, so it can be concluded that H0 is rejected, and H1 is accepted. This also means that there is a significant positive correlation between variable